Viral disruption of the blood-brain barrier - Spindler, Katherine R. (2012)
The blood-brain barrier (BBB) provides significant protection against microbial invasion of the brain. However, the BBB is not impenetrable, and mechanisms by which viruses breach it are becoming clearer. In vivo and in vitro model systems are enabling identification of host and viral factors contributing to breakdown of the unique BBB tight junctions. Key mechanisms of tight junction damage from inside and outside cells are disruption of the actin cytoskeleton and matrix metalloproteinase activity, respectively. Viral proteins acting in BBB disruption are described for HIV-1, currently the most studied encephalitic virus; other viruses are also discussed.